THE EFFECTS OF ORGANIZATIONAL CULTURE AND LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE - Lenita Waty (Jurnal Ekonomis, 2019)
The aim of this study was to find out the influence of the organizational culture and leadership style on employee performance at Sekolah Advent Cimindi and Sekolah Advent Naripan in Bandung, West Java, Indonesia. This study used quantitative approach, and the questionnaire was specifically designed. Path analysis was used to determine whether there were direct effects and indirect effects of intervening variables. The population of this study was the employees of the Sekolah Advent Cimindi and Sekolah Advent Naripan with total 35 samples. The data was collected through questionnaire using Likert scale measurement. The research instrument used in this study was validity and reliability test. The results showed that the organizational culture and the dimensions of leadership style had a positive and significant influence, both directly and indirectly on the performance of the employees. The study findings prove that organizational culture and leadership style is an important element that greatly affect employee performance. Based on the result, it is recommending that the leaders at Sekolah Advent Cimindi and Sekolah Advent Naripan need to find out the suitable and most encouraging organizational culture and leadership style so the employees are able to perform their best.